Algebraic Effects for Functional Programming - Leijen, Daan (2016)
Algebraic effect handlers, are recently gaining in popularity as a purely functional approach to modeling effects. In this article, we give an end-to-end overview of practical algebraic effects in the context of a compiled implementation in the Koka language. In particular, we show how algebraic effects generalize over common constructs like exception handling, state, iterators and async-await. We give an effective type inference algorithm based on extensible effect rows using scoped labels, and a direct operational semantics. Finally, we show an efficient compilation scheme to common runtime platforms (such as JavaScript, the JVM, or .NET) using a type directed selective CPS translation.